2016
DOI: 10.1016/j.infbeh.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Infant patterns of reactivity to tactile stimulation during parent-child interaction

Abstract: Touch is the primary modality infants use to engage with the world; atypical responses to tactile stimuli may indicate risk for disordered outcomes. The current study examined infants’ responses to tactile stimulation within parent-child interaction, adding to prior knowledge based on parent report. Nine-month-old infants (N = 497) were observed while parents painted and pressed infants’ hands and feet to paper to make designs. Positive and negative affect and gazing away, exploring, and resistance behaviors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 69 publications
(120 reference statements)
0
13
0
Order By: Relevance
“…In line with this idea, McGlone et al (2014) propose that a failure of the CT system to develop could have a significant impact on brain development, facilitating, for instance, the expression of ASD (McGlone et al 2014). This association is also supported by findings showing that responses to touch in early social interactions may provide an important cue for identifying children at greater risk for social impairments related to autism spectrum behaviours (Mammen et al 2015(Mammen et al , 2016. In line with this hypothesis, in a recent study, Kaiser et al (2015) reported that children and adolescents with ASD show a reduced activation in response to gentle CT-touch over brain areas involved in social information processing, suggesting again a potential dysfunction in neurobehavioural social development and its link with critical periods of tactile experiences early in life.…”
Section: Impaired Perception Of Affective Interpersonal Touchmentioning
confidence: 86%
See 1 more Smart Citation
“…In line with this idea, McGlone et al (2014) propose that a failure of the CT system to develop could have a significant impact on brain development, facilitating, for instance, the expression of ASD (McGlone et al 2014). This association is also supported by findings showing that responses to touch in early social interactions may provide an important cue for identifying children at greater risk for social impairments related to autism spectrum behaviours (Mammen et al 2015(Mammen et al , 2016. In line with this hypothesis, in a recent study, Kaiser et al (2015) reported that children and adolescents with ASD show a reduced activation in response to gentle CT-touch over brain areas involved in social information processing, suggesting again a potential dysfunction in neurobehavioural social development and its link with critical periods of tactile experiences early in life.…”
Section: Impaired Perception Of Affective Interpersonal Touchmentioning
confidence: 86%
“…Skin-to-skin contact at birth is a standard practice in many country, and it has been shown to promote successful breastfeeding and to improve developmental outcomes following preterm birth (e.g. Moore et al 2016;Feldman et al 2014). As evidence of the pivotal role of interpersonal affective touch for early development, a recent ERP study with preterm neonates recorded the presence of stronger brain responses to light air puff on the palm of the hand after skin-to-skin human contact, such as breastfeeding and massage, compared to painful early experiences such as injections and tube insertions (Maitre et al 2017).…”
Section: A Touch Of Love: the Role Of Interpersonal Affective Touch Imentioning
confidence: 99%
“…Is this commonality shared through genetic, environmental, or epigenetic transmission? Or perhaps mothers are sensitive to whether their child enjoys touch ( Mammen et al, 2016 ) and adjust their behaviors accordingly. In short, it is difficult to establish whether variation in maternal behavior is causing differential developmental outcomes in children, or vice versa, as both partners are known to mutually influence one another.…”
Section: Introductionmentioning
confidence: 99%
“…Future research should also seek to clarify the relationship between affectionate touch and relevant parent and infant characteristics. More broadly, parent–infant interactions involving touch may vary based on the personality and temperament of the partners ( Mammen et al, 2016 ; Beebe and Lachmann, 2017 ). Similarly, both touch and oxytocin alter brain activity in different ways depending on the relational context ( Ellingsen et al, 2016 ; Baettig et al, 2019 ), which highlights the importance of including measures of attachment in studies of affectionate touch.…”
Section: Discussionmentioning
confidence: 99%